Draft resistance at the University of Wisconsin Madison : an examination of the American Friends Service Committee - Kayser, Eric Allen (My University, 2008)
The American Friends Service Committee dedicated itself to the pursuit of peace, particularly during the Vietnam Era. During the Era of Vietnam, the University of Wisconsin-?Madison was a tense and hostile environment with protests and violence to the point of bombing the university science building. During this intense period, the AFSC approved the establishment of a unit in the Madison area that would later be referred to as the Madison Area Committee. This was associated with many community projects, but also became known for its actions against the war and the draft. The MAC would become notable for its program involving conscientious objector (C.O.) counseling and later became associated with its draft counseling. In addition to counseling, the MAC was also responsible for creation of the ?Get War Off Campus? (GWOC) group, which involved itself in a number of activities against the military on campus. However, the MAC did have some cracks in its faade related to issues in its identity. This crisis of identity was common throughout many groups and not just restricted to the MAC. Eventually as the Vietnam War came to a close, so did the draft and the need for draft resistance. As this continued, the movement began to disintegrate until very few organizations remained.
Keywords: Vietnam War, 1961-1975--Wisconsin--Madison.; Get War Off Campus (Organization); American Friends Service Committee. Madison Area Committee.; University of Wisconsin--Madison--History.; Peace movements--Wisconsin--Madison.